Faktor-Faktor Yang Berhubungan Dengan Kelengkapan Pencatatan Imunisasi Oleh Kader Posyandu Di Desa Makamhaji, Kelurahan Kartasura, Dan Desa Pucangan Kecamatan Kartasura - Yuliyati Eka Dewi, Wahyu; , Purwanti, SKM., M.Kes; , Anisa Catur Wijayanti, S.KM.,M.Epid (2016)
One means to anticipate or prevent disease in infants is needed Posyandu role. IHC is an important tool in the community that supports realizing reduction in child mortality and improving maternal welfare. Kader Posyandu is a person who because of his skill or ability to be appointed, elected or appointed to take part in activities and coaching Posyandu, and has received training ealth. Posyandu very important role with regard to the ompleteness of the recording of immunization. With the completeness of immunization records, expected development of infants can terkontrol.Penelitian aims to determine what factors are associated with a complete recording of immunization by health cadres in the village Makamhaji, Kartasura village, the village of the District Pucangan Kartasura. This research is an analytic observational study with cross sectional design and approach point time approach. The study populations were all volunteers who work to fill SIP posyandu Makamhaji Village, Village Kartasura Pucangan village, while the samples are 32 cadres Posyandu with total sampling technique. Collecting data using a questionnaire and a check list were analyzed using chi square test. Conclusion of the study are (1) there is relationship between knowledge of cadres in the ompleteness of the recording of immunization IHC (p-value 0.000), (2) there is a relationship between the motivation of cadres in the completeness of the recording of immunization IHC p-value 0.025), and (3) there is a relationship between supervision in the completeness of the recording of immunization IHC (p-value 0.009).